Plant Glutathione Biosynthesis: Diversity in Biochemical Regulation and Reaction Products - Galant, Ashley; Preuss, Mary L.; Cameron, Jeffrey; Jez, Joseph M. (Frontiers in Plant Science, 2011)
In plants, exposure to temperature extremes, heavy metal-contaminated soils, drought, air pollutants, and pathogens results in the generation of reactive oxygen species that alter the intracellular redox environment, which in turn influences signaling pathways and cell fate. As part of their response to these stresses, plants produce glutathione. Glutathione acts as an antioxidant by quenching reactive oxygen species, and is involved in the ascorbate-glutathione cycle that eliminates damaging peroxides. Plants also use glutathione for the detoxification of xenobiotics, herbicides, air pollutants (sulfur dioxide and ozone), and toxic heavy metals. Two enzymes catalyze glutathione synthesis: glutamate-cysteine ligase (GCL), and glutathione synthetase (GS). Glutathione is a ubiquitous protective compound in plants, but the structural and functional details of the proteins that synthesize it, as well as the potential biochemical mechanisms of their regulation, have only begun to be explored. As discussed here, the core reactions of glutathione synthesis are conserved across various organisms, but plants have diversified both the regulatory mechanisms that control its synthesis and the range of products derived from this pathway. Understanding the molecular basis of glutathione biosynthesis and its regulation will expand our knowledge of this component in the plant stress response network.